Literature Review: Dampak Academic Burnout pada Mahasiswa dalam Pembelajaran Hybrid terhadap Kesehatan Mental - Aisha Fadia Salsabilla; Sujarwo Sujarwo; Desy Safitri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to examine the impact of academic burnout on students’ mental health in the context of hybrid learning through a literature review approach. The rapid transformation of learning systems in higher education, particularly the integration of online and offline methods, has increased academic demands and adaptation challenges for students. This condition potentially triggers academic burnout, which is characterized by emotional exhaustion, depersonalization, and decreased academic achievement. This research employs a literature review method by analyzing relevant scientific articles published between 2019-2025 obtained from indexed national journals and open-access sources. The findings indicate that academic burnout is still commonly experienced by students, generally at a moderate level, and has a significant impact on mental health, including increased stress, emotional fatigue, and decreased academic performance. The study also identifies several influencing factors, including internal factors such as self-efficacy and hardiness, as well as external factors such as social support, learning environment, and academic workload. Furthermore, technological developments, particularly Artificial Intelligence, have the potential to be utilized as an early detection and prevention tool for academic burnout. This study implies the importance of developing adaptive learning strategies and psychological interventions to support students’ well-being in hybrid learning environments.